2021
DOI: 10.1002/bkcs.12388
|View full text |Cite
|
Sign up to set email alerts
|

To inorganic nanoparticles via nanoclusters: Nonclassical nucleation and growth pathway

Abstract: Nanoclusters, intermediates in size between atoms and nanoparticles, have been a topic of great interest because of their unique molecular structures and optical properties as compared to those of nanoparticles and bulk counterparts. Recent mechanistic studies have shown that the nanoclusters appear in the initial stages of the nanoparticle growth. The formation of nanoclusters is supported by the nonclassical nucleation theory, revealing that the nanoclusters with extremely large surface areas can be stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 179 publications
1
6
0
Order By: Relevance
“…We confirmed that the added Zn precursors passivate the surface of the InP tetrapod by measuring X‐ray photoelectron spectroscopy and quantitatively analyzed the elemental composition (In, P, Cl, Zn) of the InP tetrapod NCs according to various feed ratios of ZnCl 2 to InCl 3 . (Table 1) The In/P ratio in all samples was measured around 1.2, indicating InP NCs have an In‐rich surface and this ratio is matched well with previous report 5 . The ratios of Cl/In and Zn/In were linearly (1:1) increased with higher Zn/In feed ratio, it might be passivated with the reduction form of ZnCl acting as a Z‐type ligand, which could be reduced such as aminophosphine or oleylamine.…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…We confirmed that the added Zn precursors passivate the surface of the InP tetrapod by measuring X‐ray photoelectron spectroscopy and quantitatively analyzed the elemental composition (In, P, Cl, Zn) of the InP tetrapod NCs according to various feed ratios of ZnCl 2 to InCl 3 . (Table 1) The In/P ratio in all samples was measured around 1.2, indicating InP NCs have an In‐rich surface and this ratio is matched well with previous report 5 . The ratios of Cl/In and Zn/In were linearly (1:1) increased with higher Zn/In feed ratio, it might be passivated with the reduction form of ZnCl acting as a Z‐type ligand, which could be reduced such as aminophosphine or oleylamine.…”
Section: Methodssupporting
confidence: 91%
“…with a bulk band gap of 1.35 eV. However, the synthesis of III–V NCs is more difficult and complicated for high quality of NCs as compared to that of II–VI NC because III–V NCs have more covalent bonding characteristics than II–VI NCs 3–8 . In this regard, controlling of surface defects is challenging in III–V NCs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three quaternary and quinary compounds BaZn 1.76-Cu 0.24 Sb 2 , BaZn 1.58 Cu 0.42 Sb 2 , and Ba 0.91 Sr 0.09 Zn 1.70 Cu 0.30 Sb 2 were successfully synthesized by the molten Pb-metal flux method, and their isotypic crystal structures were carefully characterized by powder X-ray diffraction (PXRD) as well as single crystal x-ray diffraction (SXRD) analyses. [13][14][15][16][17][18][19][20][21] A series of DFT calculations 16,22,23 using the tight-binding linear muffin-tin orbital (TB-LMTO) method 24 was also performed to understand their electronic structures. Moreover, the resultant density of states (DOS), crystal orbital Hamilton population (COHP) curves, and electron localization function (ELF) diagrams were also thoroughly discussed to elucidate the effect of the co-substitution using both of the Sr-and Cu-substitutions on the electrical transport property.…”
Section: Introductionmentioning
confidence: 99%